The effects of the Xijiao Dihuang decoction combined with Yinqiao powder on miRNA-mRNA profiles in mice infected with influenza a virus - Ke Li; Xiaoming Chen; Jing Zhong; Hehe Ye; Shujing Zhang; Dongyu Ge; Xudan Wang; Ying Wu (BMC, 2020)
Abstract Background MicroRNAs (miRNAs) play vital roles in acute inflammatory and antiviral responses during influenza A virus (IAV) infection. The Xijiao Dihuang decoction combined with Yinqiao powder (XDY) is applied to remedy viral pneumonia in China and its therapeutic efficacy in pneumonic mice challenged with IAV was demonstrated; however, the underlying mechanisms remain elusive. Thus, this study aimed to explore the miRNA-mRNA profiles in the lungs of IAV-infected mice and investigate the therapeutic mechanisms of XDY involving miRNAs and associated pathways. Methods We detected the cellular miRNA contents in the lungs of mice treated with XDY (23 g/kg/d) for A/FM/1/47 (H1N1) (FM1) infection at 4 days postinoculation (dpi) and 7 dpi. MiRNA and mRNA high-throughput sequencing analyses, and miRNA and mRNA qRT-PCR analyses were used to detect and verify the relevant miRNAs and mRNAs. Conjoint analysis, GO enrichment analysis, and KEGG database analysis were applied to identify the miRNA-mRNA regulatory relationships. Results The quantities of differentially expressed miRNAs and mRNAs were upregulated over time. The data showed that 104 miRNAs and 3485 mRNAs were differentially expressed after challenge with FM1 on day 4, while 191 miRNAs and 6126 mRNAs were differentially expressed on day 7. The GO enrichment analysis and KEGG database data showed that the differentially expressed miRNAs and mRNAs were mainly enriched in JNK activity, MAPK phosphatase activity, and the TLR, Jak-STAT and TNF signalling pathways after treatment of FM1 infection with XDY. Generally, the expression trends of differentially expressed miRNAs and mRNAs based on the qRT-PCR results exhibited good consistency with the results of the high-throughput sequencing analysis. Conclusions MiRNAs and mRNAs were differentially expressed during FM1 infection. The therapeutic mechanisms of XDY in FM1-infected mice, might be related to regulating antiviral immunity and ameliorating excessive inflammatory responses by modulating the expression of dysregulated miRNAs and mRNAs involved in the ERK/JNK-AP-1, and IFN-β/STAT signalling pathways.